Synchronising Adat and Sharia in Marriage: A Case Study in Indonesia - Wahyudi, Achmad; Marlina, Yuli; Muniri; Muhammad Ghufron; Wafi , Abdul (VRISPRAAK : International Journal of Law, 2023)
Marriage is a social institution that reflects the fusion of local and religious values in Indonesia. This article explores the synchronisation between customs and Islamic law in the conduct of marriage, focusing on case studies of Javanese and Bugis customs. A qualitative approach is used to identify patterns of harmonisation as well as challenges faced. The findings show that traditions such as siraman, midodareni, mappacci and panai can be harmonised with Islamic values, despite the challenges of traditions that are not in line with sharia and high costs. This article emphasises the importance of the role of ulama and traditional leaders in building dialogue and understanding to create sustainable harmony between custom and sharia, thus enriching marriage practices in Indonesia.